Positive Periodic Solutions of a Periodic Discrete Competitive System Subject to Feedback Controls - Ronghua Tan; Zuxiong Li; Qinglong Wang; Zhijun Liu (Journal of Applied Mathematics)
Species living in a fluctuating medium and human exploitation activities might result in the duration of continuous changes. Such changes can be well-approximated as feedback controls. In this contribution a periodic discrete competitive system subject to feedback controls is proposed. By using the methods of discrete inequality, fixed point theorem, and analysis techniques, a good understanding of the existence and global asymptotic stability of positive periodic solutions is obtained. Some numerical investigations are provided to verify our analytical results.